(3fRgI GdfahS hGdCHOGf aj JhGQjN GdReGfs - (3Ydj Hf OGhO Hf EHQGgje, fhQ GdOjf GdLhGgQj, GdeYQha HGHf GdUjQaj, hjbGd dg GHf OGhO,J (B900 (3g` s
(3ChdgG (B:s
(3GdcdGe Ydi JhdjI fXGe Gdedc Gdedc GdXGgQ CHj SYjO HQbhb Hf CfjS GdYKeGfi GdjdHZGhi GdLQcSi Chd edhc GdLQGcSg s
(3BNQgG (B:s
(3aSGd GdYah aCeQ Hg hGYJbd HGdHQL ai bdYI GdLHd hbO PcQfG Cfg bOe ai ChGNQ GdSfI GdeGVjI hfRd YfO GdCejQ ebHd GdOGhOGQ hai GdeMQe CaQL Yf GdCejQ HQSHGfi s
(3LRA efg eQJH Ydi GdSfjf ef SfI (B784 - 823 (3g` cJH HNW eged GdfbW bdjdkG hHgG fXGe GdJYbjHIs
(3ai GdeYgO fSNI CNQi HQbe (B1284 (3JGQjNs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B89s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B53 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B2 - (3bSe (B5 - (3U (B206 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs